2009
DOI: 10.1590/s0102-86502009000600005
|View full text |Cite
|
Sign up to set email alerts
|

Study of acute hepatotoxicity of Equisetum arvense L. in rats

Abstract: The oral treatment with graded doses of Equisentum arvense L. was not able to produce hepatic changes. Further studies are necessary to evaluate the chronic hepatotoxicity of Equisentum arvense L. in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 7 publications
(11 reference statements)
2
9
0
1
Order By: Relevance
“…These levels of ALP were comparable to those recorded for two studies of Equisetums toxicity in rats ( (Tago et al, 2010;Baracho et al, 2009).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These levels of ALP were comparable to those recorded for two studies of Equisetums toxicity in rats ( (Tago et al, 2010;Baracho et al, 2009).…”
Section: Discussionsupporting
confidence: 85%
“…Acute hepatoxicity was not observed in our study, which utilized doses of Equisetum ramossisemum extract at 500, 250, and 125 mg/kg. However, a study has shown that high doses of Equisetum arvense in rats produced significant hepatic damage (Baracho et al, 2009). In contrast, another study found that regular doses of Equisetum arvense have a hepatoprotective effect in rats (Baracho et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Our experimental data confirm the ethnopharmacology and traditional use of E. arvense as a diuretic, which occurs worldwide, including in Brazil and other South American countries [5, 10, 16–18, 25, 30] and in several European [4, 6–9, 11, 25] and Asian countries [4, 13–15, 24]. These results represent a major stimulus for further clinical studies of the other pharmacological effects of E. arvense and other medicinal plants with broad scopes in traditional medicine.…”
Section: Resultssupporting
confidence: 80%
“…Preclinical studies have revealed various pharmacological actions of Equisetum arvense , including antioxidant [11, 13] and antidiabetic [14, 15] properties, but no acute hepatotoxicity [16]. …”
Section: Introductionmentioning
confidence: 99%
“…Hepatic tissue samples were collected for the anatomopathologic analysis. The anatomopathologic exam of the hepatic tissue showed lobular structure, however, there was no significant change in the activities of the hepatic enzymes when compared to control group [111].…”
Section: Side Effects Contraindications and Toxicitymentioning
confidence: 69%